Agarwood (A. malaccensis) leaf as an alternative Halal source of anti-inflammatory compounds - Zainurin, Nur Aimi Aliah; Hashim, Yumi Zuhanis Has-Yun; Eissa, Manar (International Institute for Halal research and Training (INHART), IIUM, 2018)
The long-term consumption of aspirin and non-aspirin non-steroidal anti-inflammatory drugs (NSAIDs) which are used to control the symptoms of inflammation and pain have been reported to cause various side effects. Thus, natural compounds of various plant species including Aquilaria malaccensis have been explored as an alternative therapeutic source for inflammation treatment with regard to their safety and effectiveness. Despite the accelerating rate on the research of agarwood leaf, the scientific evidences to elucidate the proclaimed pharmacological activities particularly anti-inflammatory activity are still limited. Therefore, it is the interest of this study to investigate the anti-inflammatory activity of A. malaccensis leaf extracted using Soxhlet method. Result showed that A. malaccensis leaf extract (ALEX) with ethanol (B) as solvent gave higher yield (mg/g) of 98.330 ± 4.113 (9.83% wt/wt) as compared to hexane (A); 24.039 ± 5.268 (2.40% wt/wt) after 6 hours of extraction. GCMS analysis revealed that 25 and 30 compounds were detected in ALEXA and ALEXB respectively with phytol as the major compound in both extracts. Subsequently, in-vitro study showed that the extracts exhibited a concentration dependent inhibition of protein (albumin) denaturation throughout the concentration range of 400-16 000 μg/ml tested. Further research is warranted to investigate the anti-inflammatory activities of A. malaccensis leaf extracts and their mechanism of action as a basis for future formulation of halal and natural anti-inflammatory agents.